Estudo do potencial genotóxico, citotóxico e antitumoral do composto Cloreto de cis-tetraaminodiclororutênio(III) sobre diferentes células tumorais - LIMA, Aliny Pereira de (2010)
Current inorganic drugs such cisplatin and related compounds widely used in the treatment cancer, however its application is limited by its severe toxicity and drug resistence. These limitations have prompted a search for news metal-based antitumor agents. Ruthenium (III) complexes represent a new family of promising metal-based anticancer drugs. In the present study, was investigated in vitro the effects of the compound on cell viability, cintetics cell cycle phases, mechanisms of apoptosis and DNA damage on tumors cells. Results of the viability using MTT reduction test and the trypan blue exclusion assay on K-562 cells revealed that this compound significantly reduced the viability of the K-562 tumors cells (IC50 approximately 10.74 and 73.45 μM), respectively, moreover viability assays on A549 lung tumor cells showed that cis-(dichloro)tetrammineruthenium(III) induced effect moderate this cell lines (IC50 > 383 μM). Additionally was observed that this compound exhibits little cytotoxicity towards MRC-5 normal human fibroblast cells (IC50 > 383 μM) when compared to K562 tumor cell line (IC50 10.74 μM). Clonogenic Assay was performed on A549 cells, and observed that lower concentrations (0.38 and 3.8 μM) cis-(dichloro)tetrammineruthenium(III) diminished colony forming ability and highest concentrations (95 and 383 μM) no colony was observed. In cell cycle analysis on K-562 and S180 tumor cells cistetrammineruthenium( III) induced change in the distribution the cell cycle phase since that % of cells entering G1, S and G2 was decreased, correlating with increase in the proportion of cells in the sub-G1-peak (indicating apoptosis). In the analysis of damage to the DNA molecule of S180 cells using the comet assay, it was observed that the ruthenium compound induced damage to the DNA molecule to both treatments (24 and 48 h) as evidenced by an increase in damage index. In addition, cis-[RuCl2(NH3)4]Cl treatment induced apoptosis in cells K-562 as evidenced for increased DNA content in the sub-G1 peak (75.35%) and a significant increase in caspase-3, 8 and 9 activity. In tumor cells S180 the apoptosis was demonstrated for by a increase numbers of Annexin V-positive cells and fragmentation DNA. Taken together, these findings strongly demonstrate that cis-[RuCl2(NH3)4]Cl exerts antitumor activity and this activity correlates with DNA damage, process apoptotic and change cell cycle.